Discovery and Characterization of (R)‑6-Neopentyl-2-(pyridin-2-ylmethoxy)-6,7-dihydropyrimido[2,1‑c][1,4]oxazin-4(9H)‑one (PF-06462894), an Alkyne-Lacking Metabotropic Glutamate Receptor 5 Negative Allosteric Modulator Profiled in both Rat and Nonhuman Primates - Stepan, Antonia F; Claffey, Michelle M; Reese, Matthew R; Balan, Gayatri; Barreiro, Gabriela; Barricklow, Jason; Bohanon, Michael J; Boscoe, Brian P; Cappon, Gregg D; Chenard, Lois K; Cianfrogna, Julie; Chen, Laigao; et al. (Journal of medicinal chemistry, 2017)
We previously observed a cutaneous type IV immune response in nonhuman primates (NHP) with the mGlu5 negative allosteric modulator (NAM) 7. To determine if this adverse event was chemotype- or mechanism-based, we evaluated a distinct series of mGlu5 NAMs. Increasing the sp3 character of high-throughput screening hit 40 afforded a novel morpholinopyrimidone mGlu5 NAM series. Its prototype, (R)-6-neopentyl-2-(pyridin-2-ylmethoxy)-6,7-dihydropyrimido[2,1-c][1,4]oxazin-4(9H)-one (PF-06462894, 8), possessed favorable properties and a predicted low clinical dose (2 mg twice daily). Compound 8 did not show any evidence of immune activation in a mouse drug allergy model. Additionally, plasma samples from toxicology studies confirmed that 8 did not form any reactive metabolites. However, 8 caused the identical microscopic skin lesions in NHPs found with 7, albeit with lower severity. Holistically, this work supports the hypothesis that this unique toxicity may be mechanism-based although additional work is required to confirm this and determine clinical relevance.